Comparison of the mandibular bone densitometry measurement between normal, osteopenic and osteoporotic postmenopausal women. - Leila Khojastehpour; Sara Mogharrabi; Mohammad Hossein Dabbaghmanesh; Nariman Iraji Nasrabadi (Tehran University of Medical Sciences, 2013)
This study was conducted to compare the mandibular bone density between postmenopausal women with normal skeletal bone mass density (BMD) and those with low skeletal BMD using digital panoramic radiographs.One hundred fifteen postmenopausal women were divided into normal and osteoporotic/osteopenic groups. Digital panoramic radiographs were prepared using Digora PCT Sorodex equipment and Promax panoramic X-ray unit (Planmeca, Helsinki, Finland, Kvp=68 and mA=9). The mandibular bone density of an area (approximately 4×4 mm), exactly near the distal edge of the right mental foramen was determined in digital panoramic radiographs using Digora for Windows (DfW) Software.There was no statistically significant difference in mandibular bone density between the normal and osteoporotic/osteopenic participants (P >0.05). Mandibular bone density was not statistically different in normal and osteoporotic individuals with SBMD or FBMD T-score -2.5 (P >0.05). Density of the region of interest differed significantly between the normal and the osteoporotic group with SBMD and FBMD T-score -2.5 (P